COMPLEX PTSD: PSYCHOTHERAPY OF PROLONGED TRAUMATIZATION - MARIA A. PADUN (Moscow State University of Psychology and Education, 2021)
The article considers a new diagnostic category — complex post-traumatic stress disorder (CPTSD), introduced into the International Classification of Diseases (ICD-11). Differences in the mechanism of influence of situational and prolonged trauma are analyzed. CPTSD diagnostic criteria are compared to PTSD and BPD (borderline personality disorder) symptoms. The term “disturbances in self-organization” is analyzed, which explains the main mechanism of the impact of complex trauma and includes emotional dysregulation, disturbances in self-perception and relationships. Psychotherapeutic approaches developed for PTSD were shown to be insufficient for the treatment of CPTSD. The article reviews an approach to CPSTD therapy based on the consensus of experts in the field of post-traumatic stress and its possible limitations are discussed. “Component based psychotherapy” — another approach to CPTSD therapy — is described. Specific features of psychotherapy for complex trauma are discussed.